Evaluation of the Effectiveness of Income Tax Policy in the era of Globalization - Loso Judijanto; Olyvia Rosalia; Selly Swandari; Firayani Firayani (PT. Anagata Sembagi Education, 2025)
Tax policies play a crucial role in shaping economic growth and investment decisions in an increasingly globalized world. This study examines the impact of globalization on national tax policies, focusing on tax competition, corporate taxation, and the challenges of maintaining revenue stability. Globalization has intensified tax competition among countries, often leading to reduced corporate tax rates to attract foreign investments. While tax incentives can stimulate economic activity, they may also erode government revenues and create disparities in tax burdens. This research explores the role of international tax treaties in harmonizing tax regulations and reducing tax avoidance strategies by multinational corporations. Furthermore, the study highlights the transition from income-based to consumption-based taxation as a response to shifting economic dynamics. The findings suggest that policymakers must balance tax competitiveness with sustainable revenue generation to ensure economic stability. By analyzing recent tax reforms and policy adaptations, this study provides insights into the complexities of taxation in a globalized economy and offers recommendations for future tax strategies.